An Innovative Technique for Recording Picture‐in‐Picture Ultrasound Videos. (1st August 2013) - Rajasekaran, Sathish; Finnoff, Jonathan T.
Abstract : Many ultrasound educational products and ultrasound researchers present diagnostic and interventional ultrasound information using picture‐in‐picture videos, which simultaneously show the ultrasound image and transducer and patient positions. Traditional techniques for creating picture‐in‐picture videos are expensive, nonportable, or time‐consuming. This article describes an inexpensive, simple, and portable way of creating picture‐in‐picture ultrasound videos. This technique uses a laptop computer with a video capture device to acquire the ultrasound feed. Simultaneously, a webcam captures a live video feed of the transducer and patient position and live audio. Both sources are streamed onto the computer screen and recorded by screen capture software. This technique makes the process of recording picture‐in‐picture ultrasound videos more accessible for ultrasound educators and researchers for use in their presentations or publications.